2018
DOI: 10.1002/jcb.28273
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in infected wound healing in type 1 diabetic rat by the synergistic effect of photobiomodulation therapy and conditioned medium

Abstract: We investigated the effects of photobiomodulation therapy (PBMT) and conditioned medium (CM) of human bone marrow mesenchymal stem cells (hBM-MSC) individually and/or in combination on the stereological parameters and the expression of basic fibroblast growth factor (bFGF), hypoxia-inducible factor (HIF-1α), and stromal cell-derived factor-1α (SDF-1α) in a wound model infected with methicillin-resistant Staphylococcus aureus (MRSA) in diabetic rats. CM was provided by culturing hBM-MSCs. Type 1 diabetes mellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
0
34
0
1
Order By: Relevance
“…T1DM rats. 25 Only PBM and PBM + curcumin increased fibroblast levels. administration on skin injury repair in an STZ-induced T1DM rat model.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…T1DM rats. 25 Only PBM and PBM + curcumin increased fibroblast levels. administration on skin injury repair in an STZ-induced T1DM rat model.…”
Section: Discussionmentioning
confidence: 98%
“…Table lists the primers used to amplify cDNA. For each sample, we produced three replicates for each target gene …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that photobiomodulation (890 nm, 80 Hz, 0.324 J/cm 2 ) meaningfully hastened the repair of injured skin at the maturation step and significantly decreased colony forming units (CFUs) of bacteria in a non-genetic model of DM2 in rats 26 .More than 100 recognized factors are involved in the insufficiency of wound healing in patients with DM2 27 . The use of a mixture of therapeutic agents and biological biostimulators could assist with treatment of non-healing wounds and show a synergistic effect to improve the success of healing in different wound models [28][29][30] .In the present study we focused on the effects of photobiomodulation and ADS, alone and combined, on the maturation step of an ischemic, delayed healing, infected wound model in DM2 rats. The combined application of photobiomodulation and ADS could hasten the healing process and provide a treatment for severe cases of DFUs in patients with DM2.…”
mentioning
confidence: 99%
“…More than 100 recognized factors are involved in the insufficiency of wound healing in patients with DM2 27 . The use of a mixture of therapeutic agents and biological biostimulators could assist with treatment of non-healing wounds and show a synergistic effect to improve the success of healing in different wound models [28][29][30] .…”
mentioning
confidence: 99%